2021
DOI: 10.1108/ijshe-02-2021-0067
|View full text |Cite
|
Sign up to set email alerts
|

The usual discourse of sustainable development and its impact on students of economics: a case from Czech higher education context

Abstract: Purpose In recent decades, the concepts of sustainable development (SD) and sustainability have become a part of the everyday information flow. Is there real impact on students who have potential to become stakeholders and decision-makers? To be able to answer this question, the authors focussed on the following problems: whether the discourse of SD has any impact on students of economics concerning their knowledge of the environmental pillar of SD; and whether it has an impact on their individual value orient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Others focused on specific subjects (Arnold, 2022; Gálvez-Rodríguez et al , 2017). Some explored sustainability perceptions among economics students (Aikowe and Mazancova, 2023; Buchtele and Lapka, 2022; Delgado et al , 2020; Gallardo-Milanés et al , 2018), not considered for this study. This resulted in 28 university case studies outlined in the methods section, identified through combined searches on WoS (Figure 3) and Google.…”
Section: Resultsmentioning
confidence: 99%
“…Others focused on specific subjects (Arnold, 2022; Gálvez-Rodríguez et al , 2017). Some explored sustainability perceptions among economics students (Aikowe and Mazancova, 2023; Buchtele and Lapka, 2022; Delgado et al , 2020; Gallardo-Milanés et al , 2018), not considered for this study. This resulted in 28 university case studies outlined in the methods section, identified through combined searches on WoS (Figure 3) and Google.…”
Section: Resultsmentioning
confidence: 99%
“…Despite this shared understanding, other aspects of environmental knowledge reveal significant discrepancies. Montenegrin students exhibit a greater appreciation for the principles of sustainable development [111], suggesting a possibly more integrated approach to sustainability in their education or national policy, as compared to their peers in North Macedonia. Conversely, students from North Macedonia demonstrate a more acute awareness of the direct effects of human activities on climate change, which may reflect direct engagement with or education about the global impacts of local actions [5], possibly driven by different environmental experiences or curriculum focuses [38].…”
Section: Discussionmentioning
confidence: 99%
“…A central starting point is that the path to sustainability is a common path with society, but especially for each individual who must acquire the basic knowledge to actively implement sustainability. is the way [3]. One of the reasons for the slow and partial integration of sustainable practices in universities is the educational community's lack of understanding and concern for environmental issues.…”
Section: Introductionmentioning
confidence: 99%